2023
DOI: 10.3390/ijms24021710
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1α Promotes Chondrocyte Autophagy through CXCR4/mTOR Signaling Axis

Abstract: SDF-1α, the most common isoform of stromal cell-derived factor 1, has shown vital effects in regulating chondrocyte proliferation, maturation, and chondrogenesis. Autophagy is a highly conserved biological process to help chondrocytes survive in harsh environments. However, the effect of SDF-1α on chondrocyte autophagy is still unknown. This study aims to investigate the effect of SDF-1α on chondrocyte autophagy and the underlying biomechanism. Transmission electron microscope assays and mRFP-GFP-LC3 adenoviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Furthermore, it has been demonstrated that the CXCL12/CXCR4 axis promotes autophagy through the MiR-125b microRNA, which thus functions as an important downstream mediator upon the activation of the CXCL12/CXCR4 axis [ 42 ]. In addition, CXCL12 plays a significant role in the induction of autophagy in chondrocytes through the activation of the CXCR4/mTOR signalling axis [ 43 ]. In particular, accordingly to our data, the authors demonstrated that CXCR4 induces autophagy by reducing the phosphorylation level of mTOR [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been demonstrated that the CXCL12/CXCR4 axis promotes autophagy through the MiR-125b microRNA, which thus functions as an important downstream mediator upon the activation of the CXCL12/CXCR4 axis [ 42 ]. In addition, CXCL12 plays a significant role in the induction of autophagy in chondrocytes through the activation of the CXCR4/mTOR signalling axis [ 43 ]. In particular, accordingly to our data, the authors demonstrated that CXCR4 induces autophagy by reducing the phosphorylation level of mTOR [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CXCL12 plays a significant role in the induction of autophagy in chondrocytes through the activation of the CXCR4/mTOR signalling axis [ 43 ]. In particular, accordingly to our data, the authors demonstrated that CXCR4 induces autophagy by reducing the phosphorylation level of mTOR [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…And dynamin‐related protein 1 (Drp1), and fission 1 protein (Fis1) are among the essential proteins responsible for mitochondrial fission processes 19 . Recent reports have revealed significant advancements in mitochondrial dynamics through characterizing the key regulators involved in mitochondrial fusion and fission 20,21 . The Adenosine monophosphate‐activated protein kinase (AMPK) signalling plays significant roles in mitochondrial morphology 22 .…”
Section: Introductionmentioning
confidence: 99%
“… 19 Recent reports have revealed significant advancements in mitochondrial dynamics through characterizing the key regulators involved in mitochondrial fusion and fission. 20 , 21 The Adenosine monophosphate‐activated protein kinase (AMPK) signalling plays significant roles in mitochondrial morphology. 22 AMPK acts as a metabolic sensor, governing mitochondrial dynamics and maintaining energy balance.…”
Section: Introductionmentioning
confidence: 99%